Analisis Kinerja Dinas Pariwisata Dan Kebudayaan Kabupaten Manggarai Barat Dalam Pengelolaan Gua Batu Cermin - Harsiana, Filomena; Arida, I Nyoman Sukma; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i01.p14, 2021)
West Manggarai Regency is one of the super priority tourism destinations development program from Central Government Republic of Indonesia. West Manggarai Regency is part of the East Nusa Tenggara Province with tourism potential namely natural, beach and cultural potential. Tourism development of tourism in West Manggarai provides positive expectations for the welfare of the local community. The existing condition of West Manggarai shows that tourism policy has not brought changes to the economic value of West Manggarai Regency. The purpose of this study is to align policy plans with the implementation of tourism development policies in West Manggrai Regency. This type of research is qualitative research, data collection techniques through observation, interviews and documentation. Determination of informants in this study using a purposive sampling technique. Analysis of the data used is qualitative descriptive. The results of the analysis of tourism development policies in West Manggarai, are inseparable from the four tourism pillars contained in the regional tourism development master plan (RIPPARDA) of West Manggarai Regency, namely the development of tourism destinations, the development of the tourism industry, the development of tourism marketing, and the development of tourism institutions. The implementation of policies in accordance with the directions of the RIPPARDA has not been maximally implemented in the tourism sector. Communities pursue changes in welfare through economic value, but all require time and process so that tourism planning and development can be felt by local people. Keyword : tourism policy, torusim development, west manggarai